Faktor - Faktor Yang Berhubungan Dengan Kejadian Tinea Pedis Pada Pemulung Di TPA Jatibarang Semarang - Kurniawati, Ratna Dian; Suhartono, Suhartono; Hanani D., Yusniar (Jurnal Kesehatan Lingkungan Indonesia, 2006)
ABSTRACT Background : Tinea pedis is a parasit disease caused by the dermatopoyd fungi and found on skin  around sole of foot and toe. Several risk factors of Tinea pedis are as follow: wearing the shoes for whole day, wearing the sock while working, and hight exposure of fungi. The aim of this research was to determine relationship between the living environment and  the incidence of Tinea pedis on "Pemulung" (the collector of abandoned goods) at the final disposal place of Jatibarang in Semarang. And also to know  the relationship between practise of personal-hygiene and the incidence of Tinea pedis on "Pemulung" . Methods : This was an observational research using cross sectional approach. Samples were "Pemulung" at the final disposal place of Jatibarang in Semarang. Number of samples taken were 56 persons. Independent variables were type of floor, source of water, wearing the shoes while working, wearing the sock while working, changing of the sock, washing the foot after working, drying the foot after washing, washing the shoes after wearing, frequency of taking a bath everyday, and wearing the sandal at home. Results : Results of regression logistic analysis showed that the factors, which influence the occurrence of Tinea pedis, were: sources of water and wearing the sandal at home. With p value for  source of water is 0,016 and wearing the sandal at home is 0,039. The efforts that can be done to prevent transmission of Tinea pedis such as: avoid using the river water and using the monitoring well. "Pemulung" should wear the sandal at home in order to reduce transmission of fungi. Beside that, they should keep clean at around their home to prevent growth of Tinea pedis fungi. Key words : Environmental Sanitation, Practise of Personal-Hygiene, Tinea Pedis